Nutritional care is a human right: incorporating principles into clinical practice - Gil Hardy (Indonesian Nutrition Association, 2024)
The landmark Vienna Declaration (VD), initiated by the international human rights working group (IHRWG) and endorsed by more than 75 professional societies acknowledged that nutritional care is a human right alongside the right to food and the right to health. In a series of position papers the IHRWG have elaborated on the commitments required for translating human rights and ethical principles into clinical practice.1-3 The ultimate objective of the VD is to ensure all patients have a right to be screened and diagnosed for disease related malnutrition (DRM) then to receive evidence based artificially administered nutrition and hydration (AANH) administered by an interdisciplinary team of experts to positively impact clinical outcomes and survival. Unfortunately, nutritional care in hospitals and post discharge is frequently below standard and is not part of the patient's holistic care.2 Reasons include; inadequate education of healthcare professionals (HCPs), lack of malnutrition awareness, no reimbursement for nutrition treatments, or absence of public health policy.2,4